Analisis Visual Gim Cuphead - Persada, Satria Indra Praja (Universitas Komputer Indonesia, 2020)
Video games are one of the visual communication design works that are in great demand right now, interactive games have advantages over other design works because they can be played by users and interact directly with objects in the video game, now there are lots of video games in the market with various types ranging from RPG (Role Palying), Adventure, fighting to Racing with various games and Visual concepts, one of which is Cuphead, Cuphead itself is an adventure game that offers unique visual concepts so that it can attract gamers in buying the game, Cuphead itself has sold 5 million copies, this cannot be separated from the unique Visual concept that is carried by Cuphead. The research on the Cuphead Game is based on the visual concept carried by the Cuphead game where the visual concept carried by the Cuphead game uses the visual concept of retro cartoon, while the purpose of this research is to find out the visual elements contained in the game and the method used in the research is a descriptive analysis method where the object of this research will be divided according to the elements contained there in, then a literature study is conducted on each of these elements and an analysis is carried out so that the elements of the elements can be identified, then the results of the research this is an overview and expertise of the element so that it impacts the designer or game developer so that he can consider the visual concept and the visual elements that are stretched so that the game has its own characteristics so that it can compete with other game developers.